Occupational radiation monitoring and quality assurance in hospital X-ray departments. (Journal of Science and Technology, 2016)
Quality assurance is essential to any programme of diagnostic radiology, to prevent undue exposure of x-ray personnel and patients to radiation.This paper reports observations from a survey of some hospital x-ray facilities in Accra and Kumasi in Ghana, to find out about steps taken by x-ray workers to ensure quality control and administration in diagnostic radiology.The grid point method has been used to do a detailed study of scatter radiation levels of two x-ray departments in Accra.The iso-dose rate contours have been analysea, and results show the importance of good design of x-ray rooms and provision of protective structures.